Pelaksanaan Pemberian Informasi dan Kelengkapan Informed Consent di Rumah Sakit Umum Daerah Bangkinang (RSUD Bangkinang) - Haryani Octaria; Wen Via Trisna (STIKes Hang Tuah Pekanbaru, 2016)
Informed consent is an agreement given by the patient or his who is entitled to medical doctors to perform a the act of medical towards patients after obtain information complete and that this belief that about the act. This study attempts to of the provision of information and completeness informed consent in the district general hospital bangkinang (RSUD Bangkinang) .The kind of research this is qualitative approach quantitative method. Technique data collection observation and guidelines. Technique data analysis was conducted using technique quantitative and qualitative analysis. The results of the study that a groove for granting information is in line with the theory that is . Completeness for charging identity patients to address patients 14 ( 14.6 % ) unfilled complete. It also applies to completeness charging identity responsible for patients to address 25 ( 26.0 % ) filled complete. Completeness for charging autentikasi a patient to kind of action medical 39 ( 40.6 % ) filled complete, and also for charging the medical term 45 ( 46.9 % ) filled complete, so are the name and signature witness i from the patients 52 ( 54.2 % ) filled complete. This conclusion that is a groove for granting information already exists , started from inpatient rooms doctor give information to with a patient prior to the act of medical. In completeness identity included in a category not good , and comprehensiveness of autentikasi included in a category less baik.dengan advice expected to director of the hospital to heed completeness informed consent in contents of by doctors and nurses that to fill with complete